(untitled) (Research, Society and Development, 2023)
Dens invaginatus (DI) is a developmental dental anomaly where there is an invagination of the enamel organ in the dental papilla, before calcification is complete. These anomalies are clinically relevant, as bacteria from the oral cavity can contaminate and propagate within these malformations, leading to the development of early caries and, consequently, pulp death. The definitive cause of these anomalies is still uncertain. The reported frequency is 0,04-10%. And the permanent lateral incisors are the most affected, followed by the central incisors, premolars, canines and molars, in descending order. ID is usually diagnosed on a routine radiograph, however reconstructed CBCT images are useful in assessing the true nature of the invagination-root canal relationship. The objective of this case report was to present an endodontic technique for the treatment of a compromised DI. Recognition of root canal developmental anomalies and complexities is essential for long-term success in endodontic therapy. Modification of the conventional treatment procedure is often necessary for unusual canal anatomy. For this reason, referral to an endodontic specialist is always indicated.